2008
DOI: 10.1177/0192513x08329293
|View full text |Cite
|
Sign up to set email alerts
|

Making Space for Graduate Student Parents

Abstract: Work—family issues of graduate students are nearly invisible, despite record numbers of men and women in graduate school during their peak childbearing years. Furthermore, very little is known about what, if any, services are available for graduate student parents. In this article we describe the theoretical and practical tensions between society's view of idealized mothering and academia's vision of graduate students as idealized workers. We then present results of a survey about parental supports for graduat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 14 publications
4
129
0
4
Order By: Relevance
“…Women are expected to invest considerable time, emotion and energy in their children (Danna Lynch 2008;Douglas and Michaels 2004;Hays 1996), as well as to demonstrate a sense of devotion and self-sacrifice (Arendell 2000). This construction of parenthood affects men and women, but is mostly about the latter due to the long-standing association of women with care (Springer, Parker, and Leviten-Reid 2009). While theories of maternal deprivation (Bowlby 1953) may have been invalidated a long time ago, the view that parents, particularly mothers, are the best person to look after a child remains widespread in this context (European Values Study 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are expected to invest considerable time, emotion and energy in their children (Danna Lynch 2008;Douglas and Michaels 2004;Hays 1996), as well as to demonstrate a sense of devotion and self-sacrifice (Arendell 2000). This construction of parenthood affects men and women, but is mostly about the latter due to the long-standing association of women with care (Springer, Parker, and Leviten-Reid 2009). While theories of maternal deprivation (Bowlby 1953) may have been invalidated a long time ago, the view that parents, particularly mothers, are the best person to look after a child remains widespread in this context (European Values Study 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Work in academia keeps intensifying and, as for parenting, has become the subject of an increased surveillance (Calvert, Lewis, and Spindler 2011), while groups that had historically been excluded from academia moved to its margins and, for some, to its centre (Mirza 2009). Students, especially doctoral students, are expected to work intensively, attend conferences, undertake administrative duties and provide research assistance to academics (Springer, Parker, and Leviten-Reid 2009). Expectations in terms of mobility and availability risk conflicting with parental commitments.…”
Section: Introductionmentioning
confidence: 99%
“…Student mothers must negotiate the presumed conflicts between the binaries of mother/student, good mother/good student, as well as the socially constructed narrative of the "good" versus "bad" mother (DuquaineWatson, 2017;Lynch, 2008). Literature on student mothers focus primarily on the graduate level (Castañeda & Isgro, 2013;González, 2007;Lynch, 2008;Springer, Parker, & Leviten-Reid 2009), with little attention to community college student mothers, rendering them "unexplored and, as such, an unacknowledged population" (Oliva & Jimenez, 2017, p. 239 145). Deficit ideologies range from blaming student mothers for poor judgment for pursuing an education while deciding to have children, to cultural stereotypes and beliefs that single student mothers are bad mothers (Cunningham, 2013;Duquaine-Watson, 2017 vilified as "bad mothers" and "bad immigrants" (Escobar, 2016;Meacham, 2016, para 12).…”
Section: Latina Student Mothers In Higher Educationmentioning
confidence: 99%
“…Moreau and Kernot (2015) found that only one of their 10 case studies of UK universities collected data on student parents. What research literature there is highlights the invisibility of student parents despite their significant and growing numbers, and tends to focus on the tensions and challenges of combining being a parent (particularly a mother) with completing an academic qualification (Armenti, 2004;Kurtz-Costes et al, 2006;Springer et al, 2009;Marandet and Wainwright, 2010). At this juncture the generic research on the student parent may illuminate potential issues and future research on the international student parent (Martens and Grant, 2008;NUS, 2009;Marandet and Wainwright, 2010;Moreau and Kernot, 2015).…”
Section: Visibility Of Students' Familiesmentioning
confidence: 99%